Analisis Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Keputusan Pembelian di Aneka Usaha Percetakan Area Printing - Gustini Gustini; Azuwandri Azuwandri; Samsul Akmal (STIA Bengkulu, 2023)
This study aims to determine the effect of service quality and product quality on purchasing decisions partially. The sampling method is purposive sampling method with a sample of 100 respondents. The analytical method used is quantitative analysis. The results showed that partially the service quality variable had a positive and significant effect, the product quality variable had a positive and significant effect. The coefficient of determination shows that 88.8% of service quality variables and product quality affect purchasing decisions, while the remaining 11.2% is influenced by other variables not examined.